Hormone plasma levels from pituitary-gonadal axis in performance athletes after the 400 m run - Slowinska-Lisowska, M.; Majda, J. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: The aim of this study was to compare the concentration changes in hormones from pituitary - gonadal axis, induced by the 400 m run in the well-trained athletes (vice-champions in the Hall and Summer Athletic World Championship in 1999) to the changes observed in the competitors with shorter training period and achieving worse final results. METHODS: This research was conducted on 6 males - members of the Polish Olympic Team, who won vice-championship in the Hall and Summer World Championships 1999 and 6 athletes trained in the academic sport clubs. In the recent investigation, the 400 m run was assumed to be a stimulating impulse for evoking hormonal changes. The blood samples were taken from the elbow vein before the run, immediately after the effort and after the 24-hour rest. In the serum, the luteinizing hormone (LH), follicle-stimulating hormone (FSH), total testosterone (TT), free testosterone (FT) as well as the sex hormones-binding globulin (SHBG) concentrations were determined. RESULTS: During our research, immediately after the 400 m run in group I - the top class sportsmen - the statistically significant increase in both gonadotrophins (LH, FSH) was determined as well as the decrease in the total and free testosterone. In the group II - the athletes with the lower training level - the increase in FSH and the total and free testosterone concentrations was noticed. There were no statistically significant differences in the SHBG concentration. After-effort increase in the lactic acid concentration was observed in both groups. In the master group I, the increase in lactic acid concentration was higher than in group II. In both groups after the 24-hour restitution, the examined parameters, except LH levels in the group I, showed the concentrations similar to those before the effort. Analysis of the time needed to cover the distance of the race showed that the athletes from group I covered the distance of 400 m in the shorter time. CONCLUSIONS: The group of master class athletes, whose average intensive training period was 8 years, had higher VO2max and higher after-effort increase in the lactic acid concentration than in the group of sportsmen with the shorter training period (4 years), who had lower VO2max, worse sport results and lower after-effort increase in the lactic acid concentration, gave different hormonal response (particularly TT, FT concentration) for the same exercise impulse. The difference based on the fact, that after the run in group I the decrease in the total and free testosterone levels and in group II the increase in the same parameters were observed. The observed hormonal changes in the master class athletes induced by the years-long anaerobic training might provide evidence for the reduction of functional reserves in gonads when compared to the group of less trained sportsmen.